Kajian Suhu Pengeringan dan Ketebalan Irisan Terhadap Mutu Tepung Batang Tanaman Buah Naga (Hylocereus sp.) - Ifmalinda, Ifmalinda; Harjuniati, Weni; Andasuryani, Andasuryani (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Cactus plants include the stems of dragon fruit plants (Hylocereus sp.), which have nutrients that may be good for human health. These can also be used to make flour because they have the ability to replace wheat flour by up to 25% and have been used in a variety of processed goods, including noodles, yoghurt, cakes, puddings, cookies, and jelly drinks Abundant dragon fruit plant stems will come to waste if not utilized optimally, so it is necessary to process dragon fruit stems by processing them into flour. One of the stages of making flour is drying, which aims to remove the water content of the material to a certain extent to get maximum results and can extend the shelf life of flour. This study aimed to examine the effect of the appropriate drying temperature and slice thickness on the quality of dragon fruit stem flour using a rack-type oven with gas as a heat source. This study used an experimental method with a Completely Randomized Design arranged in a factorial manner consisting of 2 factors: drying temperature and slice thickness. The results showed that the best treatment was at a drying temperature of 60°C with a thickness of 2 mm, as seen from the observations, namely the relative humidity of 28,51 and the fineness modulus of 1,030.